Large disturbance stability analysis method for DC microgrid with virtual DC motor control - Fengzhan Zhao; Ting Liu; Yuntao Ju; Hong Li (IET Renewable Power Generation)
Abstract Mixed potential theory is frequently employed for analysing large‐disturbance stability. The precision of the current stability criterion for DC microgrids controlled by virtual DC motors (VDCM), which relies on mixed potential theory, is inadequate. This is primarily because the criterion does not account for the control parameters of the DC bus voltage control link and the virtual DC motor link. To address these issues, the paper initially formulates the control aspect of the VDCM using a controlled current source. Subsequently, it derives the system's mixed potential function from the model, enabling the development of a stability criterion that includes the control parameters of the DC bus voltage control link, the virtual DC motor link, and the current tracking link. It also clarifies how parameters not directly included in the criterion affect system stability. Through simulations and experimental validations, it is demonstrated that the proposed stability criterion effectively captures the impact of control parameters on system stability and precisely delineates the system's power stability boundary, offering insights for system parameter optimization.